Computing Amplify-and-Forward Relay Amplification Factor to Improve Total Capacity at Destination - Al-Khalid, Hj Othman; Bello, Olalekan; Hushairi, Zen; Khairuddin, Abdul Hamid (Science Publications, 2015)
In this study, we propose a new Amplify-and-Forward (AF) amplification factor to improve the error performances of the current AF schemes and thus enhance the total capacity at the destination terminal. The proposed scheme has two degrees of freedom, meaning that it contains two variable parameters that can simultaneously vary the amplification factor instead of one as in traditional variable-gain or semi-blind relaying. The numerical results show that the proposed AF scheme outperforms some current ones with which it is compared in terms of average capacity and probability of outage and thus brings AF relaying performances closer to that of Decode-and Forward (DF) strategy which hitherto outperforms it. The results also show that by increasing or decreasing the power share of the relay, the optimal location of the relay is not only moved closer to or farther away from the destination, the total averag.